Study guides

☆☆

Q: What is the answer -2x 48-3x-3x2x 6 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

Firstly, write it as a mathematical equation:3x + 6 = 2x + 10Subtract 6 from both sides:3x = 2x + 4Subtract 2x from both sides:x = 4

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

6 - 3x = 4 - 2x 6 = x + 4 x = 2 Check it. 6 - 6 = 4 - 4 It checks.

6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2

Related questions

If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

2x + 3x + 6 = 5x + 6

2x-5=3x+6 -5-6=3x-2x -11=x x=-11

2x+3=3x-3 2x-3x=-3-3 -x=-6 x=6

Firstly, write it as a mathematical equation:3x + 6 = 2x + 10Subtract 6 from both sides:3x = 2x + 4Subtract 2x from both sides:x = 4

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

If 3x + 3 = 2x + 6 then 3x - 2x = 6 - 3 x = 3

5x+(6-3x)+8=5x+6-3x+8=2x+14 2x + 14

-3x + 2x > 6 -x > 6 x < 6 {x| x < 6 } or ( -∞, 6)

2x - 5x = -6 -3x = -6 3x = 6 x = 6/3 x = 2 By Mohammed Arafat

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

People also asked